THE HUMAN FACTOR IN THE ECONOMIC DEVELOPMENT OF SOCIETY - Gulnoza Nasrullaeva (Western European Studies, 2024)
The topic of the human factor, the problem of its formation, is very relevant today for countries that are transitioning from a traditional society to a modern society, from an industrial-raw economy type to an industrial-innovation type. In addition, due to the enormous efforts spent on the development of the education system and health care system, which are the most basic infrastructure of the human factor, the problems of human capital formation and the work done should be known to the general public
Keywords: formation; development; enormous